Peningkatan Disiplin Siswa Melalui Pembelajaran Kooperatif Pada Praktik Pembelajaran Penjaskes di Sekolah Dasar - Deananda, Aura Nova; Putri, Ivanka; Aniyah, Ainun; Adinata, Hasrudi (Jurnal Ilmiah Wahana Pendidikan, 2025)
In Indonesia, teachers' ability to undertake research is still below average. This is due to a lack of research knowledge and experience among teachers. As a result, teachers rarely conduct research and have never published a scientific paper. As a result, mentoring in the form of formal training in research competence is required. There is, however, no training structure designed expressly for instructors to improve their research competency. The goal of this study is to create a training system that will eventually improve instructors' research skills. The research and development process is based on a modified Dick & Carey development model. As a result, an upgraded teacher competency training system including training modules, training agendas, teaching books, and learning videos has been developed and tested by specialists. Teachers in Indonesia are expected to use the training system to increase their research skills.